Technical Report: Factors affecting the adoption of climate-smart aquaculture (CSAq) in North Central Coast of Vietnam - Cao Le Quyen; Trinh Quang Tu; Phan Phuong Thanh (2019)
Under the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), the Vietnam Institute of Fisheries Economics and Planning (VIFEP), WorldFish, and Thanh Hoa Agricultural Extension Centre had successfully implemented the pilot project “Enhancing community resilience to climate change by promoting climate smart aquaculture practices along the coastal areas of the North Central of Vietnam” (ECO-SAMP). From 2015-2017, the project was implemented by introducing sanility domesticated tilapia in improved extensive system of tiger shrimp in Hoang Phong commune, Thanh Hoa province. This technical report documents the follow-up activities that has been carried out by VIFEP in 2018 to find the out key factors influencing the adoption of climate-smart aquaculture (CSAq) in North Central Coast of Vietnam.